Macroporous 3D MXene architecture for solar-driven interfacial water evaporation - Ju, Maomao; Yang, Yawei; Zhao, Jianqiu; Yin, Xingtian; Wu, Yutao; Que, Wenxiu (Journal of advanced dielectrics, 2019)
Interfacial water evaporation through solar heating with photothermal materials is a promising strategy for seawater desalination and wastewater purification. Tightly packed 2D membranes with high reflection losses and limited vapor escape channels result in a low evaporation rate. In this work, 3D MXene architecture was fabricated by dropping the delaminated Ti3C2 ( d -Ti3C2) nanosheets onto the carbonized melamine foam (CMF) framework. Owing to the macroporous 3D architecture, more effective broadband solar absorption and vapor escaping were achieved. As a result, the 3D CMF@ d -Ti3C2-based evaporator delivers a water evaporation rate of 1.60 kg/m2 ⋅ h with a solar-to-vapor conversion efficiency of up to 84.6%.